Juridical Analysis of the MS Glow Vs. Brand Dispute PS Glow Based on RI Supreme Court Decision Number 161 K/Pdt.Sus-HKI/2023 - Alfi Quthni Aswad (Journal AGENCY, 2025)
Even though the law regarding brands has been regulated and made easier, in reality brand disputes often occur in our country. Plagiarism of product and service brands is a case that often occurs in brand disputes. One example is the trademark dispute between MS Glow vs. PS Glow. The problems in this research are (1) how are trademark disputes resolved in Indonesia? (2) What are the legal protection efforts for trademarks in Indonesia? and (3) what are the judge's considerations in the Supreme Court decision number 161 K/PDT.SUS-HKI/2023? This research is normative juridical research using a statute approach and a case approach. The conclusions of this research are (1) trademark dispute resolution can be carried out through litigation, non-litigation, arbitration and the Trademark Law approach; (2) legal protection efforts for trademarks are carried out using preventive, repressive and geographical indication approaches; and (3) the judge's considerations in the Supreme Court decision number 161 K/PDT.SUS-HKI/2023 do not focus on whether or not a product can use a name that is cut from the registered brand name. As in the case of "MS GLOW" which registered their brand with the name "MS GLOW/For beautiful skincare" while in promotional activities they only used "MS GLOW". Apart from that, the judge's decision also started from inappropriate considerations when linking two cases, namely the Medan Commercial Court Decision with the Surabaya Commercial Court Decision. Even though the two decisions have different subject and object cases.